2018
DOI: 10.1002/jsde.12237
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polyethylene/Polypropylene Glycol Ethers of Fatty Alcohols for Micelle‐Mediated Extraction of Calendula anthodium

Abstract: Classical extraction methods used for the isolation of active substances from the plant materials are expensive, complicated, and often environmentally unfriendly. The ultrasonic assisted micelle‐mediated extraction (UAMME) method seems to be an interesting alternative. In this study, Calendula anthodium UAMME extract composition and antioxidant properties were examined. Several nonionic surfactants, from the group of ethoxy/propoxylated fatty alcohols, were applied in the extraction process. The results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The simulations were performed in triplicate, and the final results are the arithmetic average of the set of results, while the structures are the result of clustering. Previously, this methodology was successfully applied to study the incorporation of flavonoids into non-ionic surfactant micelles [50,51].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The simulations were performed in triplicate, and the final results are the arithmetic average of the set of results, while the structures are the result of clustering. Previously, this methodology was successfully applied to study the incorporation of flavonoids into non-ionic surfactant micelles [50,51].…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was concluded that the polyphenol content decreases with the decreasing number of PEG/PPG groups in the surfactant structure. In the case of the antioxidant activity and the flavonoid content, there was no such relationship [5]. Since the dependence of the UAMME extraction yield on the surfactant structure has not yet been clearly explained, for further studies, we selected compounds with different carbon chain lengths but the same polyether group (two subsets: O20, S20, CS20 and CS12, T12, LT12 in Table 2) and with a diverse number of oxyethylene units but a fixed alkyl chain length (O5, O10, O20 in Table 2).…”
Section: Extractionmentioning
confidence: 92%
“…The surfactants' physicochemical properties (Table 1) indicated that besides O5 they are highly hydrophilic surfactants with very good surface properties and low CMC values. Moreover, from this set, only O5 and possibly O10 could potentially be used in CPE technology due to the cloud point below 50 • C. So far, the results revealed that non-ionic surfactants belonging to polyethers of fatty alcohols mainly affect the efficiency of flavonoid extraction from plant material [5,6,12,16]. The extremely effective eluent for flavonoids extraction from Bidens tripartite was the aqueous solution of C9-11 Pareth-5 (Rokanol ® NL5, HLB = 8.6), i.e., the most hydrophilic among the studied Rokanols ® .…”
Section: Extractionmentioning
confidence: 93%
See 2 more Smart Citations